English for Specific Purposes Teaching in Current Academic Atmosphere in Digital Era in STIES Mitra Karya - Noviarini, Tiara (JELT: Journal of English Language Teaching, 2025)
This study investigates the dynamics of English for Specific Purposes (ESP) instruction at STIES Mitra Karya within the current digital academic environment. With the integration of digital platforms such as Learning Management Systems (LMS) and the adoption of blended learning approaches, ESP teaching has evolved to become more flexible, contextualized, and aligned with the professional needs of students in the fields of economics and business. Employing a descriptive qualitative methodology, data were collected through interviews, observations, and documentation analysis. The findings reveal that digital technologies have significantly enriched the learning process, enhancing accessibility and engagement. However, challenges persist, particularly regarding infrastructure limitations, digital literacy gaps, and the readiness of human resources. Institutional support, including the provision of training programs, network enhancement, and innovation incentives, is identified as critical to the successful transformation of ESP teaching. This study emphasizes the need for sustainable strategies to ensure the ongoing effectiveness and resilience of ESP instruction in the digital era.